The relationship between social network body size and the body size norms of Black and Hispanic adults - Ginger Winston; Erica Phillips; Elaine Wethington; Martin Wells; Carol M. Devine; Janey Peterson; Brian Wansink; Rosio Ramos; Mary Charlson (Preventive Medicine Reports, 2015)
Objective: To examine the relationship between the body size norms of Black and Hispanic adults and the body sizes of their social network members. Methods: Egocentric network data were examined for 245 adults recruited from 2012–2013 in New York City. A multivariable regression model was used to examine the relationship between participants' perception of normal body size and the body sizes of their network members adjusted for participant age, education, race/ethnicity and network size. Participants' body size norms were also examined stratified by the following characteristics of obese network members: frequency of contact, living proximity, relationship, and importance of relationship. Results: Index participants were 89% female with mean body mass index 33.5 kg/m2. There were 2571 network members identified (31% overweight, 10% obese). In the fully adjusted multivariable model, perception of normal body size increased as the number of network members with obesity increased (p < 0.01). Larger body size norms were associated with increased frequency of contact with obese network members (p = 0.04), and obese members living in the home (p = 0.049). Conclusions: These findings support a relationship between the body size norms of Black and Hispanic adults and their social network body size.